2020
DOI: 10.3389/fphar.2020.00863
|View full text |Cite
|
Sign up to set email alerts
|

Antiplatelet Agents Have a Distinct Efficacy on Platelet Aggregation Induced by Infectious Bacteria

Abstract: Platelets are the cornerstone of hemostasis. However, their exaggerated aggregation induces deleterious consequences. In several diseases, such as infectious endocarditis and sepsis, the interaction between platelets and bacteria leads to platelet aggregation. Despite platelet involvement, no antiplatelet therapy is currently recommended in these infectious diseases. We aimed here, to evaluate, in vitro, the effect of antiplatelet drugs on platelet aggregation induced by two of the bacterial pathogens most inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 36 publications
2
15
0
Order By: Relevance
“…The neutrophil phagocytic assay showed that the difference of the neutrophil phagocytic rate of L. paracasei LP10266 and L. paracasei ATCC25302 was statistically significant ( p = 0.044). Platelet aggregation caused by bacteria is an important source of infective endocarditis [ 31 ]. Many Gram-positive bacteria causing sepsis have been shown to induce platelet aggregation [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The neutrophil phagocytic assay showed that the difference of the neutrophil phagocytic rate of L. paracasei LP10266 and L. paracasei ATCC25302 was statistically significant ( p = 0.044). Platelet aggregation caused by bacteria is an important source of infective endocarditis [ 31 ]. Many Gram-positive bacteria causing sepsis have been shown to induce platelet aggregation [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Heying et al (2019) proposed that the bactericidal properties of ticagrelor could resemble the aspirin effect, modulating the expression of S. aureus virulence factors with a decrease in the expression of MSCRAMM's and toxins. The potential inhibitory effect of ticagrelor on bacteria-platelet interactions was further supported by an in vitro study reporting the highest inhibitory effect of bacteria-induced platelet aggregation by ticagrelor as compared to aspirin, aspirin plus ticagrelor, or tirofiban (Hannachi et al, 2020). Very recently, two studies described an inhibitory effect of ticagrelor on α-toxin mediated platelet clearance by the hepatic AMR pathways, thereby preserving the antibacterial activity of platelets (Sun et al, 2021;Ulloa et al, 2021).…”
Section: Discussionmentioning
confidence: 89%
“…The initial phase of IE development involves the interplay between platelets and bacteria (Figure 1; Hamzeh-Cognasse et al, 2015;Liesenborghs et al, 2018Liesenborghs et al, , 2019, which strongly suggests an essential role for platelets in early stages of IE. Vegetations could form either via indirect or direct interaction of bacteria with platelets (Hamzeh-Cognasse et al, 2015;Hannachi et al, 2020; Figure 1). S. aureus -bacteria interactions are mainly mediated through binding of the GPIIb/IIIa platelet receptor (integrin a IIb b 3 ) (Hamzeh-Cognasse et al, 2015;Liesenborghs et al, 2018Liesenborghs et al, , 2020.…”
Section: Why Could Targeting Platelets Be Beneficial Against Staphylococcus Aureus Infective Endocarditis?mentioning
confidence: 99%
“…Previous studies have shown that S. aureus produces fibrinogen‐binding protein, and the membrane surface protein binds to platelet receptors to cause platelet aggregation in platelet‐rich plasma at higher bacterial levels 29 . At that time, bacterial cells accumulate in the aggregates 30 . These mechanisms may reduce the bacterial concentration (even to zero) in the liquid phase of plasma by culture.…”
Section: Discussionmentioning
confidence: 99%
“…29 At that time, bacterial cells accumulate in the aggregates. 30 These mechanisms may reduce the bacterial concentration (even to zero) in the liquid phase of plasma by culture. In S. aureus-contaminated PC units, some aggregations are often found using visual inspection after day 3 and thereafter and can, thus, be excluded before transfusion.…”
Section: Discussionmentioning
confidence: 99%